Is there light at the ends of the tunnel? Wireless sensor networks for adaptive lighting in road tunnels - Ceriotti, M; Corra, M; D'Orazio, L; Doriguzzi, R; Facchin, D; Guna, S T; Jesi, G P; Cigno, R L; Mottola, L; Murphy, A L; Pescalli, M; Picco, G P; et al. (2011 10th International Conference on Information Processing in Sensor Networks, 2011)
Existing deployments of wireless sensor networks (WSNs) are often conceived as stand-alone monitoring tools. In this paper, we report instead on a deployment where the WSN is a key component of a closed-loop control system for adaptive lighting in operational road tunnels. WSN nodes along the tunnel walls report light readings to a control station, which closes the loop by setting the intensity of lamps to match a legislated curve. The ability to match dynamically the lighting levels to the actual environmental conditions improves the tunnel safety and reduces its power consumption. The use of WSNs in a closed-loop system, combined with the real-world, harsh setting of operational road tunnels, induces tighter requirements on the quality and timeliness of sensed data, as well as on the reliability and lifetime of the network. In this work, we test to what extent mainstream WSN technology meets these challenges, using a dedicated design that however relies on well-established techniques. The paper describes the hw/sw architecture we devised by focusing on the WSN component, and analyzes its performance through experiments in a real, operational tunnel.